2023
DOI: 10.29303/jppipa.v9i2.2036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guided Inquiry-Based Excretion System E-Module to Improve Critical Thinking and ICT Literacy Skills for Students

Abstract: E-Modules are teaching materials that are converted digitally by including images, videos, and animations. E-Modules can be integrated with Model Guided Inquiry. The purpose of the study was to determine the effectiveness of learning using guided inquiry-based E-Modules on students' critical thinking skills and ICT Literacy of students on the subject of the class VII excretion system of SMP 2 Ngaringan. The study population was 207 students of SMP N 2 Ngaringan, Central Java, Indonesia. The research sample use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…In addition, the results of the ANCOVA test in Table 5 indicated that the mean dispositions of students' critical thinking differed between GI-Moodle, GI-WAG, and SI-WAG implementations of e-learning. Previous research has shown that the GI learning model is successful at enhancing students' critical thinking skills, which supports the findings of this study (Indawati et al, 2023;Miftakhurrohmah et al, 2023;Pursitasari et al, 2020;Sutiani et al, 2021;Verawati et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the results of the ANCOVA test in Table 5 indicated that the mean dispositions of students' critical thinking differed between GI-Moodle, GI-WAG, and SI-WAG implementations of e-learning. Previous research has shown that the GI learning model is successful at enhancing students' critical thinking skills, which supports the findings of this study (Indawati et al, 2023;Miftakhurrohmah et al, 2023;Pursitasari et al, 2020;Sutiani et al, 2021;Verawati et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The student's critical thinking dispositions in this study were improved because of the GI model's emphasis on student activity (Margunayasa et al, 2019;Putra et al, 2018), in which students were asked to establish investigative procedures, collect data, and make conclusions (Llewellyn, 2013;Sutiani et al, 2021). Beginning with research questions (problems) given by the lecturers, students collaborated to design the procedure, data collecting, data analysis, formulate conclusions, and communicate their findings (Indawati et al, 2023;Miftakhurrohmah et al, 2023;Yuliati et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PBL-based learning will lead to meaningful learning (Abu-Ghaneema, 2018;Adams et al, 2022;Kostiainen et al, 2018). This means that PBL-based learning can improve students' critical thinking skills (Miftakhurrohmah et al, 2023;.…”
Section: Figure 3 Misfit Ordermentioning
confidence: 99%
“…In line with research conducted by (Suyatman et al, 2021a), where they experience difficulty in analyzing and formulating complex problems. These obstacles cause low critical thinking abilities in every aspect (Lapuz et al, 2020;Masruro et al, 2021;Miftakhurrohmah et al, 2023;Ramadani et al, 2021;Utami et al, 2017).…”
Section: Observation Stagesmentioning
confidence: 99%
“…The primary focus of inquiry learning is students' active involvement in discussions, their ability to formulate explanations, connect explanations with scientific theories, and communicate the results they have obtained (Anggraeni et al, 2023;Miftakhurrohmah et al, 2023). The use of the inquiry learning model has been implemented in many elementary schools.…”
Section: Problem Statementmentioning
confidence: 99%